2018
DOI: 10.1177/1744987118762992
|View full text |Cite
|
Sign up to set email alerts
|

Educating intensive care unit nurses to use central venous catheter infection prevention guidelines: effectiveness of an educational course

Abstract: Background Nurses' knowledge of central venous catheter-related infection (CVC-RI) prevention guidelines is poor, indicating that nurses do not receive proper education about these guidelines. Aim The aim of this study was to evaluate the effectiveness of an educational course that aimed to improve nurses' knowledge about CVC-RI prevention guidelines. Method A sample of 131 nurses were randomly assigned to the experimental group (received an educational course) or control group (received no education). Pre-Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
2
14
0
4
Order By: Relevance
“…Unsurprisingly, the age of the nurses was positively associated with their years of work experience and seniority in their healthcare organisation. Generally, older nurses (both in age and in years of experience) had better knowledge of both CVAD and PIV care and maintenance than their younger peers (Abu Sharour, 2018; Aloush, 2018; Bijayalaxmi et al, 2010; Cicolini et al., 2013; Dedunska & Dyk, 2015; Paolucci, Nutter, & Albert, 2011). However, it was not clear from these studies where these older nurses had obtained their knowledge (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Unsurprisingly, the age of the nurses was positively associated with their years of work experience and seniority in their healthcare organisation. Generally, older nurses (both in age and in years of experience) had better knowledge of both CVAD and PIV care and maintenance than their younger peers (Abu Sharour, 2018; Aloush, 2018; Bijayalaxmi et al, 2010; Cicolini et al., 2013; Dedunska & Dyk, 2015; Paolucci, Nutter, & Albert, 2011). However, it was not clear from these studies where these older nurses had obtained their knowledge (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Our scoping review revealed an inconsistent relationship between years in nursing practice (seniority) and VAD management knowledge. Although some studies found no relationship between years in nursing practice and VAD management knowledge (Banks, et al, 2010; Mason, Ferrall, Boyington, & Reich, 2014; Raynak et al., 2018),one found a trend towards higher knowledge scores based on employment seniority (Paolucci, Nutter, & Albert, 2011), and three studies found that experienced nurses performed significantly better than less experienced nurses (Abu Sharour, 2018; Aloush, 2018; Dedunska & Dyk, 2015). However, one study reported that older nurses performed more poorly on the knowledge tests than younger nurses (Esposito, Guillari, & Angelillo, 2017).…”
Section: Cvads—themes In the Literaturementioning
confidence: 99%
See 3 more Smart Citations